(untitled) (International journal of artificial intelligence, 2024)
This article considers the importance, methodology and practice of training primary school students in the spirit of national customs and traditions. The article explains how students can contribute to their personal development by promoting national heritage, traditions, and traditional values. Also, opinions are expressed about the role of educational institutions and the importance of educational methods in the process of primary education in the formation of national spirituality, and pedagogical approaches are presented.